Foreign-Born Argentine Soldiers: Extension of Citizenship Status and Military Professionalization in Argentina (1995-2015) - Frederic, Sabina Andrea (2017)
What was the percentage of naturalized immigrants among Argentine volunteer Army soldiers between 1995 and 2015 ? What are their national origins? How did the present state of affairs come about ? What are the modalities and issues involved in their participation in military service ? These are some of the questions this article attempts to answer in exploring the quantitative and qualitative incidence of those issues in the process of military professionalization in Argentina. In 1995, the country suspended conscription and moved to an all-volunteer military force, setting new requirements for the recruitment of soldiers. Research has so far focused basically on the opening of the armed forces to women, rather than on the impact of volunteering on the foreign-born population that, by age 24 (maximum recruitment age), had acquired Argentine citizenship. The present article is meant to fill this gap. The replacement of the lottery-based selection of recruits by a voluntary enlistment system effectively enabled naturalized citizens to serve in the armed forces. Though in comparison with other countries (US, Spain, Britain, France) the numbers involved are very small, this effective, not just nominal, move can be seen as evidence of both a more flexible relationship between the armed forces, the State and the nation at this stage of military professionalization, and a decline (as witnessed in recruitment advertising campaigns) of patriotism as a frame of reference in the Argentine military.